How Islamic Bank Managing Risk? An Emphasis on Anticipating Financial Crisis - Sebastiana Viphindrartin; Zainuri Zainuri; Muhammad Zilmi Anugrah (Universitas Negeri Surabaya, 2020)
The global economic crisis in 2008 shocked and pressured Indonesian macroeconomic and financial system stability. The decline in macroeconomic stability has an impact on banking policy in lending. Most banks in the world respond to the crisis by doing credit rationing, but how about Islamic bank response toward this condition in Indonesia? Therefore, this study aims to examine the effect of Capital Adequacy Ratio (CAR) and macroeconomic variables on the amount of Islamic banking financing in Indonesia. The method used in this study is the SVAR (Structural Vector Auto Regression) analysis method. The results showed that inflation, capital, and CAR variables had a significant effect on Islamic banks financing amount. In contrast, GDP had no significant impact on Islamic banks financing amount which means that Islamic banking in Indonesia was not implemented pro-cyclical based lending policy.